PTU-058 RFA for dysplastic barrett's oesophagus: 10-years of experience from the east midlands. Issue 2 (June 2019) - White, JR; Ortiz-Fernández-Sordo, J; Santiago-García, J; Reddiar, D; De Caestecker, J; Cole, A; Kaye, P; Ragunath, K
Abstract : Introduction: Radiofrequency ablation (RFA) is the recommended therapy for flat high grade dysplasia (HGD) and residual Barrett's oesophagus (BO) after endoscopic mucosal resection (EMR) to reduce the risk of metachronous neoplasia. We aim to assess safety and effectiveness from the East Midlands Barrett's RFA database. Methods: Data was analysed on patients referred to Nottingham University Hospital for RFA therapy to treat dysplastic BO between 2008 and 2018. The main outcome measures included complete remission of dysplasia (CRD), complete remission of intestinal metaplasia (CRIM), recurrent rates of BO, HGD and adenocarcinoma, procedural complications, treatment failure rates and median follow up prior to discharge back to the referring hospital. RFA techniques involved the use of circumferential and focal ablation every three months until the BO was obliterated. Follow up endoscopy and biopsy of original BO length was performed 3 and 12 months after the last RFA session and annually thereafter unless there was evidence of recurrent disease. Results: 221 patients were included in the analysis. Median age was 67.72 (±9.2) years, the male: female ratio was 4:1, median BO length was C2 (IQR:6) M6 (IQR:5), 59.8% had EMR prior to RFA. The proportion of patients having RFA with a previous histological diagnosis of LGD, HGD and intramucosal adenocarcinoma (IMC) was 22%, 44.8% and 32.2% respectively. The median number of RFA sessions was 3 (IQR:2). The rates of CRD and CRIM were 93.2% and 91.3%. Adjuvant ablation techniques were required in less than half of patients: APC 38% with median sessions of 1(1-4) and 1 excision biopsy session in 9.4% of patients. Severe oesophagitis delayed treatment in 12.1% and hiatus hernia repair surgery was required in 1.3% of patients. Stricture rates were 5.4% requiring a median of 2 (IQR:6) dilatations and bleeding requiring hospital admission was 0.45%. RFA failed or was abandoned in 6.3% of patients. Metachronous lesions development during RFA treatment phase warranting further therapy in 14.9% patients: BO (2.7%) LGD (0.9%) HGD (5%) and IMC (6.3%). Metachronous lesions and BO developed after CRIM in 5% requiring further therapy and 0.9% developed invasive cancer. Median follow up post CRD/CRIM was 20.1 (±28.9) months. The survival rate over the 10-year study period was 94.6% with the majority of deaths due to unrelated disease. Conclusions: This 10-year data demonstrates that RFA therapy is effective in achieving eradication of BO and dysplasia with a favourable safety profile.